(untitled) (Sustainability in Debate, 2025)
Our aim was to obtain information from users regarding the disposal location for unused or expired household medications. A descriptive, cross-sectional and prospective study was conducted with 451 patients from primary health care centres in Araçatuba, SP, Brazil. The respondents answered a pre- validated questionnaire, composed of objective questions. For data analysis, we used the chi-square association test and chi-square with Yates’ correction, with a significance level of 5%. Age is associated with the location chosen to dispose of medications, while receiving guidance on the correct place modifies certain disposal habits, with 95% confidence. Most people believe that improper disposal of medications can cause harm to the environment and to human and animal health; however, the most common way to dispose of medications is to throw them in the household waste. Consumer knowledge and practices regarding medication disposal need to be improved.